2019
DOI: 10.5194/acp-19-6535-2019
|View full text |Cite
|
Sign up to set email alerts
|

A numerical process study on the rapid transport of stratospheric air down to the surface over western North America and the Tibetan Plateau

Abstract: Abstract. Upper-level fronts are often associated with the rapid transport of stratospheric air along tilted isentropes to the middle or lower troposphere, where this air leads to significantly enhanced ozone concentrations. These plumes of originally stratospheric air can only occasionally be observed at the surface because (i) stable boundary layers prevent an efficient vertical transport down to the surface, and (ii) even if boundary layer turbulence were strong enough to enable this transport, the original… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
(60 reference statements)
0
11
0
Order By: Relevance
“…Model-based intrusion climatologies and observationbased case studies have demonstrated that high altitude regions such as the Western United States (Cooper et al, 2004b(Cooper et al, , 2011Brioude et al, 2007;Langford et al, 2009Langford et al, , 2015aLangford et al, , 2015bLangford et al, , 2017Pan et al, 2010;Lefohn et al, 2011Lefohn et al, , 2012Lefohn et al, , 2014Lin et al, 2012aLin et al, , 2015Yates et al, 2013;Škerlak et al, 2014Dolwick et al, 2015;Lin et al, 2016), the Tibetan Plateau (Ding et al, 2006;Cristofanelli et al, 2010;Chen et al, 2011Chen et al, , 2013Yin et al, 2017;Škerlak et al, 2019), and the Andes (Anet et al, 2017) are important regions for STT, not only because of frequent deep intrusions but also because their high elevation and very deep daytime boundary layers facilitate the mixing of the diluted intrusions down to the surface. Research aircraft have also documented the occurrence of stratospheric intrusions above Siberia (Berchet et al, 2013), the remote regions of the tropical and midlatitude South Indian Ocean (Clain et al, 2010;Baray et al, 2012), and at the surface of the high-altitude Antarctic ice sheet (Cristofanelli et al, 2018).…”
Section: Development Of Emissions Inventoriesmentioning
confidence: 99%
“…Model-based intrusion climatologies and observationbased case studies have demonstrated that high altitude regions such as the Western United States (Cooper et al, 2004b(Cooper et al, , 2011Brioude et al, 2007;Langford et al, 2009Langford et al, , 2015aLangford et al, , 2015bLangford et al, , 2017Pan et al, 2010;Lefohn et al, 2011Lefohn et al, , 2012Lefohn et al, , 2014Lin et al, 2012aLin et al, , 2015Yates et al, 2013;Škerlak et al, 2014Dolwick et al, 2015;Lin et al, 2016), the Tibetan Plateau (Ding et al, 2006;Cristofanelli et al, 2010;Chen et al, 2011Chen et al, , 2013Yin et al, 2017;Škerlak et al, 2019), and the Andes (Anet et al, 2017) are important regions for STT, not only because of frequent deep intrusions but also because their high elevation and very deep daytime boundary layers facilitate the mixing of the diluted intrusions down to the surface. Research aircraft have also documented the occurrence of stratospheric intrusions above Siberia (Berchet et al, 2013), the remote regions of the tropical and midlatitude South Indian Ocean (Clain et al, 2010;Baray et al, 2012), and at the surface of the high-altitude Antarctic ice sheet (Cristofanelli et al, 2018).…”
Section: Development Of Emissions Inventoriesmentioning
confidence: 99%
“…Škerlak et al . (2019) used mesoscale model simulations to study the transport pathways of stratospheric air brought into the troposphere by folds. They found that over the TP, significant vertical transport in the free troposphere is not required for high concentrations of stratospheric tracer to reach the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Research has long indicated the significance of folding to STT: localized observational and process‐based studies have demonstrated strong ozone STT within intrusions extending deep into the troposphere, while broader‐scale studies have shown folding's role in STT of air and noted the important influence of stratospheric ozone variability on tropospheric ozone (Hess et al., 2015; Langford et al., 1996, 2009; Langford & Reid, 1998; Lefohn et al., 2012; Neu et al., 2014; Ott et al., 2016; Skerlak et al., 2019; Stohl et al., 2003; Wang et al., 2020; Williams et al., 2019). However, an investigation of folding's relationship with ozone STT that is systematic and global while based on data with high chemical and meteorological fidelity is lacking, despite recent developments in coupled chemistry and meteorology products (including those not analyzed here, e.g., MERRA2‐GMI and GEOS‐CF).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The dominant mechanism for STT of air is tropopause folding (Stohl et al., 2003), wherein an intrusion of the stratosphere into the troposphere allows exchange between the two layers, typically influencing upper‐ and mid‐tropospheric ozone concentrations (Danielsen, 1968; Shapiro, 1980). Folding can also enable large stratospheric influence on near‐surface ozone in some regions—notably the eastern Mediterranean and Middle East (Akritidis et al., 2016; Tyrlis et al., 2014; Zanis et al., 2014), western United States (Langford et al., 1996, 2009; Langford & Reid, 1998; Lefohn et al., 2012; Wang et al., 2020), and Tibetan Plateau (X. L. Chen et al., 2011; X. Chen et al., 2013; Skerlak et al., 2019). But a more precise and systematic assessment of folding's role in ozone STT and relationship to tropospheric ozone than established by previous global studies (Beekmann et al., 1997; Boothe & Homeyer, 2017; Skerlak et al., 2014; Sprenger & Wernli, 2003) is possible due to new analysis tools.…”
Section: Introductionmentioning
confidence: 99%